KNOWLEDGE, ATTITUDE, PRACTICE OF ORAL HEALTH COALITION AMONG GYNECOLOGISTS AND DENTAL PRACTITIONERS IN CHENNAI - Shruthi.M; Kiran Kumar Pandurangan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Oral diseases complicate pregnancy and labor which can affect the health of the baby. Problems in oral health of women may be minimized if there is a well?coordinated knowledge, awareness and also through interdisciplinary approach between general dental practitioners and gynecologists. Therefore, the aim of this study was to assess the KAP of oral health coalition among gynecologists and general dental practitioners in chennai. A cross sectional survey was conducted among gynecologists and general dental practitioners. A standard comprehensive questionnaire was uploaded on an online survey platform and was circulated. The data were retrieved and imported to SPSS Version 20 for statistical analysis. Chi square test was performed to check for association. It was observed that among 150 participants, 74.03% dental practitioners were aware of the association between periodontal diseases and pregnancy outcomes; 58.44% of them always consulted gynaecologists before prescribing any drug to pregnant women. Similarly 53.42 % of the gynaecologists also refer their patients to dental practitioners when they mentioned any problem pertaining to oral cavity. A statistically significant association was seen for the parameters such as years of practice, gender and fields of practice (p<0.05).